Application of Fiber Bragg Grating Sensor coated with Polyaniline as an optical Sensor for chloroform detection - Ahad, Irma Zulayka Mohamad; Harun, Sulaiman Wadi; Gan, Seng Neon; Phang, Sook Wai (RAPRA Technology, 2017)
Fiber Bragg Grating (FBG) sensor coated with PAni was designed as a sensing device in chloroform detection. PAni thin film was synthesized through chemical oxidation method by using aniline (Ani) as a monomer, ammonium persulphate (APS) as an initiator and dioctyl sodium sulfosuccinate (AOT) as a dopant. The chemical structure of PAni thin film was confirmed by using Fourier transform infrared (FTIR) and ultraviolet-visible (UV-Vis) spectrometer. The conducting behaviour of PAni thin film (1.157 x 10-2 S/cm) was determined by using four-point probe measurement. In the optical sensor part, FBG was etched in hydrofluoric acid solution (48% HF) to remove the cladding layer on fiber before coated with PAni. The response of this sensor was monitored based on the different of Bragg wavelength shift at ∼1557 nm in an optical spectrum analyzer (OSA) detector. PAni-coated FBG significantly increased in the Bragg wavelength shift (sensitivity = 0.0009) compared with uncoated FBG (sensitivity = 0.0002). The interaction between PAni and chloroform was significantly confirmed by the "polaron peak ratio" (Pf/ Pi) and "quinoid and benzenoid peak ratio" (IQ/ IB) through UV-vis and FTIR spectroscopy analysis. In this study, FBG sensor coated with PAni thin film had been found as an efficient sensor in chloroform detection with fast response time (7 s).